The Analysis of Creative Tourism and Location on Tourist Satisfaction through WOM as an Intervening Variable in the Region Becici Peak Pine Forest Tour, Yogyakarta - Arohman Arohman; Henny Welsa; Muinah Fadhilah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to analyze the effect of creative toursim to WOM; the effect of location to WOM; the effect of creative tourism to tourist satisfaction; the effect of location to tourist satisfaction; the effect of creative tourism to tourist satisfaction through WOM; the effect of location to tourist satisfaction through WOM. This research was located in Bantul Regency involving visitor of Kawasan Wisata Hutan Pinus Puncak Becici Yogyakarta. The sampling technique used Slovin’s Formula method. Data analysis used in this research were descriptive analysis, inferensial analysis, and mediation analysis. The analysis tool in this research was the Partial Least Square (PLS) analysis with SmartPLS 3.2.8 software, and the mediation analysis used the Bootstrapping. The results of the analysis on hypothesis testing in this study indicate that creative tourism has a positive and significant effect to WOM; location has a positive and significant effect to WOM; creative tourism has a positive and significant effect to tourist satisfaction; location has a positive and significant effect to tourist satisfaction. The results of the bootstrapping test on mediation analysis show that WOM is unable to mediate between creative tourism and tourist satisfaction; WOM is able to mediate between location and tourist satisfaction.